2021
DOI: 10.1101/2021.07.08.21260162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity of Oxford-AstraZeneca COVID-19 vaccine in Vietnamese healthcare workers

Abstract: We studied the immunogenicity of Oxford-AstraZeneca COVID-19 vaccine in 554 Vietnamese healthcare workers who were naïve to SARS-CoV-2 infection. Neutralizing antibodies increased after each dose. The sero-conversion rate reached 98.1% after dose 2. Btu at month 3, neutralizing antibodies decreased. The requirement for a third dose warrants further research.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Antibody studies showed that among individuals who had no previous infections, IgG antibody levels were maximized approximately 4 weeks after the first dose and 2 weeks after the second dose for mRNA vaccines (104-106). Similarly, neutralizing antibodies were maximized approximately 28 days after the first dose and 14 days after the second dose of the AstraZeneca vaccine (107,108). Therefore, in any future, efficacy research focused on these vaccines, outcomes should be recorded during this period to determine the maximum possible VE.…”
Section: Time After Vaccinationmentioning
confidence: 99%
“…Antibody studies showed that among individuals who had no previous infections, IgG antibody levels were maximized approximately 4 weeks after the first dose and 2 weeks after the second dose for mRNA vaccines (104-106). Similarly, neutralizing antibodies were maximized approximately 28 days after the first dose and 14 days after the second dose of the AstraZeneca vaccine (107,108). Therefore, in any future, efficacy research focused on these vaccines, outcomes should be recorded during this period to determine the maximum possible VE.…”
Section: Time After Vaccinationmentioning
confidence: 99%